Organizational and institutional issues in climate change adaptation and risk management: Insights from practitioners’ survey in Bangladesh, Ethiopia, Kenya, and Mali - Ragasa, Catherine; Sun, Yan; Bryan, Elizabeth; Abate, Caroline; Atlaw, Alumu; Keita, Mahamadou Namori (International Food Policy Research Institute, 2013)
This report provides some reflections and insights on the level of awareness, practices, and organizational and institutional issues being faced by countries as they adapt to climate change, based on interviews with 87 practitioners working in government agencies, local organizations, international organizations, and think thanks reporting involvement in climate change adaptation. Data were collected in Bangladesh, Ethiopia, Kenya, and Mali using both an e-survey platform and face-to-face interviews.